Pharmaceutic Production of Microcrystalline Cellulose (MCC) as Tablet Excipient from Sugarcane Bagasse (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2025)
Waste from sugarcane ice milling in Langsa is abundant without processing, so it is necessary to think about its more useful utilization without causing environmental pollution. Sugarcane bagasse is one of the samples that is rich in cellulose, so it has the potential to be developed into cellulose microcrystals that can be used as a filling material in tablet making. The preparation of bagasse MCC was carried out in 2 (two) stages, namely the α-cellulose isolation stage (including delignification, swelling, and bleaching processes), and the second stage is the hydrolysis of α-cellulose using 2.5 N HCl solvent to obtain bagasse MCC. From the results of this study, the sugarcane bagasse MCC produced has physical characteristics in the form of hablur, white in color, odorless, and tasteless, has a moisture content of 3.78%, with a pH of 7, a permanganate content of 2.54% and a size of 33.843 μm. So it can be concluded that the sugarcane bagasse MCC produced has met the tablet excipient requirements as required by the Handbook of Pharmaceutical Excipients.